45 GHz stacked‐FET PA with linearising feed‐forward rectifier. Issue 18 (1st September 2016) - Kim, Y.; Lee, S.; Kwon, Y.
Abstract : A 45 GHz stacked‐FET power amplifier (PA) using 0.15 μm pseudomorphic high electron mobility transistor is presented with feed‐forward rectifier bias topology for enhancing linearity. The proposed rectifier bias circuit provides the gate‐bias voltage which allows the stacked common‐gate FET in triple‐stacked FET to have linear operation at higher power compared with the conventional fixed gate‐bias circuit. It shows improvement in linearity effectively from measured results of gain compression and third‐order intermediation. Measurements are performed by on‐wafer probe station. The fabricated 45 GHz stacked‐FET PA exhibits an output power of 18 dBm, a transducer gain of 15 dB, and a power‐added efficiency as high as 9.5%.